Organoleptic Characteristics and Nutritional Value of Gluten-Free Custard Tart Based on Beneng Taro and Black Rice Bran Composite Flour - Ksatriadi Widya Dwinugraha; Firman Muhammad Basar; Rosyda Dianah (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
The utilization of local food resources such as Beneng taro (Xanthosoma undipes K. Koch) and black rice bran (Oryza sativa L.) as wheat substitutes in pastry products offers a functional gluten-free alternative. This study aimed to analyze the organoleptic characteristics and nutritional value of gluten-free custard pie (pai susu) based on Beneng taro and black rice bran composite flour. The experimental study used a comparative method with three formulations of taro:bran flour ratios, namely F1 (70:30), F2 (60:40), and F3 (50:50). The evaluation included hedonic and hedonic quality tests involving 35 semi-trained panelist. Proximate analysis was performed on the best formula from the hedonic test results. The results showed that the composite flour proportion significantly affected the hedonic quality characteristics (color, taste, texture, mouthfeel). Based on the weighted sum method, formulation F2 (60:40) was determined as the best treatment with a "liked" acceptance level (score 4.03). The F2 custard pie exhibited a moist texture, dark brown color, and favorable taste. Proximate analysis revealed that the F2 product contained 30.08% moisture, 1.89% ash, 24.43% fat, 35.05% carbohydrate, and 8.55% protein. The high protein and energy content (394 kkal/100 g) in this product demonstrates the potential of black rice bran in enhancing the nutritional profile of gluten-free custard pies compared to conventional products.